The Impact of Social Media on Attitudes Towards Tourism - Krátki, Dániel; Berki, Tamás; Karancsi, Zoltán; Szabó, Eszter; Győri, Ferenc (Turisztikai és Vidékfejlesztési Tanulmányok, 2022)
Social media is getting an increasingly important role in acquiring tourist information fast and easily. Our study was aimed to find out to what extent social media is influential as far as the motivations of travellers are concerned, and how compelling social media content is; also, the research was aimed to identify what feelings and emotions are triggered in travellers by actually visiting the places popularized by social media. In our survey an online questionnaire was used for mapping the issues mentioned above (N=208). Our results have proven the importance of the effect of social media sites on the motivation of travellers. Also, it has been identified, that women are more active consumers of contents on social media sites, and they tend to organize their travels online more frequently, than their male counterparts. Social media users accept the information on these pages as authentic, and only a few of them have experienced disappointment when visiting the given destinations; although, men seem to be more critical and disillusioned than women. No ’compelling’ impact of the social media has been outlined, but the feeling ’FoMo’ (Fear of Missing out) has already been experienced by some of the respondents.